(untitled) (Experimental biology, 2017)
L.setulosus is offered for creation of biopreparation «Setulin», possesing he- mostatic action, the basic reactant of biopreparation is diterpen – lagochirzin. Results under the maintenance and dynamics of diterpen lagochirzin accumula- tion in various parts of L.setulosus are presented: in roots, stalks, leaves, flowers and calyx lobes during the growing season, and also results on conditions of cultivation L.setulosus in the conditions of a typical sierozem are resulted. From the obtained data is visible, that the given species of a plant is endemic. It is established, that dynamics of accumulation of lagochirzin in phytomass accrues from the beginning to the middle of the growing season. The chemical analysis of L.setulosus on a localization of lagochirzin in various organs of a plant, has shown, that the greatest quantity of lagochirzin collects in calyx lobes of the plants. Also it is established, that L.setulosus can be cultivated in the condi- tions of the typical sierozem, a mineral food is necessary for the given species of plants of Lagochilus genus, except nitric fertilizers. Comparative studying of wild-growing and cultural forms of L.setulosus has shown, that in the cultivated phytomass of plants the maintenance of lagochirzin on 17-20 % higher than in the wild-growing species.